The Existency Of Nosemparaka Manu Tradition Amid The Community In Wombo Village, Tanantovea Kecamatan, Donggala District - amalia novarita; Ferdia; Febby Gracella; Angki; Hadi Suryono (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2020)
Nosemparaka Manu is a tradition practiced by pregnant Women whose womb has reached seven months and this tradition is carried out by people from Kaili tribe. The existence of the Nosemparaka Manu tradition in these increasingly advanced times is a manifestation of the community's exception (the Kaili tribe) in maintaining ancestral beliefs or traditions. This research was conducted in Wombo Village, Tanantovea District, Donggala Regency. The purpose of this research is to find out the existence or existence of the Nosemparaka Manu tradition in Wombo Village. This study uses a survey method with qualitative data analysis. The population in this study is the entire community (Kaili tribe) of Wombo Village and the samples used or taken are ten people using purposive sampling technique (intentionally). Data collection techniques used are the method of observation, interviews, literature studies, and documentation. The results of this study indicate that the existence or existence of the Nosemparaka Manu tradition in the village of Wombo is progressing at a time of decline or decline and may even disappear in the next ten or five years. This is caused by the community's more medical trust (rational matters), many teenagers who do not know and are ignorant, sando or shamans are old and there is only one person, and no one wants to continue the mandate or knowledge.